Corporate governance as a catalyst for sustainability: insights from Malaysian Public listed companies - Normarliana Laili,; Romlah Jaffar,; Mohamat Sabri Hassan,; Ahmad Monir Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Corporate sustainability remains a prominent global concern, with stakeholders increasingly holding businesses accountable for their actions. Corporate governance (CG), facilitated by an effective board and risk management committee, can exert an impact on corporate sustainability performance (CSP). The mixed findings of prior research, on factors influencing CSP, serve to motivate this study. Additionally, the influence of sustainability committees (SC) in the CG-CSP relationship has not been examined before. This study thus represents one of the earliest investigations that elucidate the impact of SC on the relationship. The study sample comprised 762 listed companies in Malaysia, spanning 2020 to 2022. Using content analysis on company annual reports, the results established the positive and significant influence of CG on CSP as consistent with the stakeholder theory. Moreover, the results demonstratd that SC was not able to strengthen the role of CG in its relationship with CSP. These empirical findings offer valuable guides for regulators, companies, and stakeholders, that emphasise the influence of CG and SC on CSP.